2021
DOI: 10.1021/jacs.0c13352
|View full text |Cite
|
Sign up to set email alerts
|

Nonradiative Triplet Loss Suppressed in Organic Photovoltaic Blends with Fluoridated Nonfullerene Acceptors

Abstract: In organic photovoltaic (OPV) blends, photogenerated excitons dissociate into charge-separated electrons and holes at donor/acceptor interfaces. The bimolecular recombination of spin-uncorrelated electrons and holes may cause nonradiative loss by forming the low-lying triplet excited states (T1) via the intermediate charge-transfer triplet states. Here, we show that such a spin-related loss channel can be suppressed in the OPV blends with fluorinated nonfullerene acceptors (NFAs). By combining ultrafast optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 53 publications
3
79
0
Order By: Relevance
“…Other approaches in the literature include incorporation of a delayed fluorescence emitter as a ternary component [90] and fluorination of a material to increase the triplet energy level and thus hinder the triplet CT state to local triplet transition. [91] However, this approach has led to similar solar cell efficiencies for DRCN5T and 2F-DRCN5T. [33] Moreover, our work in this paper concludes that DRCN5T triplets are formed in amorphous regions; another approach could be to fabricate materials where the polaron formation is favored in more crystalline domains, thus spatially separating polarons from the triplets.…”
Section: Discussionmentioning
confidence: 61%
“…Other approaches in the literature include incorporation of a delayed fluorescence emitter as a ternary component [90] and fluorination of a material to increase the triplet energy level and thus hinder the triplet CT state to local triplet transition. [91] However, this approach has led to similar solar cell efficiencies for DRCN5T and 2F-DRCN5T. [33] Moreover, our work in this paper concludes that DRCN5T triplets are formed in amorphous regions; another approach could be to fabricate materials where the polaron formation is favored in more crystalline domains, thus spatially separating polarons from the triplets.…”
Section: Discussionmentioning
confidence: 61%
“…Thestructure of the encapsulated NDI monomer; E-NDI-T,w as determined by X-ray crystallography (single crystals grown via the layering technique using chloroform and methanol), which confirmed that the straps indeed shield the NDI core (Figure 2). Analysis of the packing shows minimum distances of % 12 between the centroids of the NDI cores (see Supporting Information), with the closest intermolecular separations being between the alkyl chains,of the order of 4 .A nalysis of the packing shows minimum distances of % 12 between the centroids of the NDI cores (see Supporting Information), with the closest intermolecular separations being between the alkyl chains,o ft he order of 4 .Incontrast, non-encapsulated NDIs often show close p-p stacking distances in the region of % 3.3 , [34] demonstrating the ability of the macrocycle to spatially separate the chromophores effectively.…”
Section: Synthesismentioning
confidence: 99%
“…Analysis of the packing shows minimum distances of % 12 between the centroids of the NDI cores (see Supporting Information), with the closest intermolecular separations being between the alkyl chains, of the order of 4 . In contrast, non-encapsulated NDIs often show close p-p stacking distances in the region of % 3.3 , [34] demonstrating the ability of the macrocycle to spatially separate the chromophores effectively.…”
Section: Synthesismentioning
confidence: 99%
“…Alongside singlet excited-state properties, those of triplet excited states are also important because they affect the charge recombination dynamics in OSCs. 26,27 Herein, we study the singlet and triplet excited-state dynamics of Y6 in solution and solid states using transient absorption (TA) spectroscopy. We found that pristine Y6 films show biphasic singlet exciton decay kinetics with decay constants of ~220 ps and ~1200 ps, which is the origin of the large discrepancies in the previously reported exciton lifetimes in the solid state.…”
Section: Toc Graphicsmentioning
confidence: 99%